Family as a Safe Space: A Descriptive Examination of Psychological Safety, Parenting Practices, and Parent–Child Emotional Relationships - Yuarini Wahyu Pertiwi; Amirul Muminin; Raihan Saputra (Green Publisher, 2026)
Social and economic changes influence the dynamics of parenting within families, particularly in meeting children's emotional and psychological needs. This study aims to describe the condition of psychological safety within families, nurturing, caring, and nurturing parenting patterns, parental mental health, and the tendency of love languages ​​in parent-child relationships during integrative parenting education activities. The study used a descriptive quantitative approach with a pretest–posttest design. The study subjects were 30 parents who participated in parenting education activities in Sukawangi Village, Sukabudi District, Bekasi Regency. Data were collected using psychological safety instruments, exploration of parenting patterns, mental health reflection through the metaphor of an emotional battery, and mapping of love languages. Then, data were analyzed using descriptive statistics with the help of JASP software. The results showed that psychological safety in families was in the moderate category, parenting patterns were dominated by aspects of compassion, parental mental health was at a moderate level of emotional energy, and the most dominant love language was physical touch. These findings indicate that psychological safety in families is formed through the interaction between parental emotional readiness, balanced parenting patterns, and how affection is expressed. This study provides an empirical picture that can be the basis for developing more holistic and contextual parenting education programs.